Three-Dimensional Cotton-Wool-Like Polyhydroxybutyrate/Siloxane-Doped Vaterite Composite Fibrous Scaffolds: Effect of Imogolite-Coating on Physicochemical and Cell Adhesion Properties - Obata, Akiko; Mori, Kazuma; Inukai, Keiichi; Kato, Katsuya; Poologasundarampillai, Gowsihan; Kasuga, Toshihiro (Frontiers in Materials, 2020)
Poly(3-hydroxybutyrate-co-4-hydroxybutyrate), P(3HB-4HB), and siloxane-doped vaterite (SiV) composite fibrous scaffolds with 3D cotton-wool-like structure were developed using an electrospinning system for use in bone tissue regeneration. Scaffolds exhibited a significantly larger fibre-fibre separation distribution than non-woven fibre mats as observed with micro-computed tomographic studies. Coating the hydrophobic P(3HB-4HB)/SiV fibres with imogolite nanotubes (INT), aluminium silicate nanotubes, made the 3D construct hydrophilic and improved water penetration into the 3D structure (~2 sec). Coating efficacy was confirmed by the detection of aluminium on the surface of fibres using scanning electron microscopy (SEM) energy dispersive spectroscopy (EDS). Dissolution experiments showed increased release of silicate ions in cell culture medium which can improve migration and mineralization of osteogenic cells inside of the 3D structure. The coating also contributed to an enhanced adhesion and migration of osteoblast-like cells (SaOS-2) within the 3D construct. The differentiation and mineralization of the cells were not affected by the coating. The coating for such cotton-wool-like structured scaffolds was effective for an enhancement of cell functions on early stages of culture. Thus, the developed materials with 3D structure, flexibility, silicate-ion release ability, and cell compatibility are expected to be good candidate materials for bone tissue regeneration.